Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/josh.13051
|View full text |Cite
|
Sign up to set email alerts
|

Low Health Literacy Is Associated With Energy‐Balance‐Related Behaviors, Quality of Life, and BMI Among Rural Appalachian Middle School Students: A Cross‐Sectional Study

Abstract: BACKGROUND: Many studies document associations between low health literacy (HL) and poor health behaviors and outcomes. Yet, HL is understudied among adolescents, particularly from underserved, rural communities. We targeted rural adolescents in this cross-sectional study and explored relationships between HL and (1) energy-balance-related health behaviors and (2) body mass index (BMI) and quality of life (QOL). METHODS:Surveys were administered to 7th graders across 8 middle schools in rural Appalachia. HL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The findings among students from our study were consistent with that have been documented in adults [ 21 ]. Moreover, although very few studies regarding HL-HRQoL association were available from children and adolescents worldwide, such a positive HL-HRQoL relationship observed in our study was also in line with that reported among children and adolescents in similar studies from Virginia of USA [ 22 ], Belo Horizonte city of Brazil [ 23 ] and Chongqing city of China [ 24 ]. However, the age-groups of participants were different between our study and the three mentioned above [ 22 24 ].…”
Section: Disscussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings among students from our study were consistent with that have been documented in adults [ 21 ]. Moreover, although very few studies regarding HL-HRQoL association were available from children and adolescents worldwide, such a positive HL-HRQoL relationship observed in our study was also in line with that reported among children and adolescents in similar studies from Virginia of USA [ 22 ], Belo Horizonte city of Brazil [ 23 ] and Chongqing city of China [ 24 ]. However, the age-groups of participants were different between our study and the three mentioned above [ 22 24 ].…”
Section: Disscussionsupporting
confidence: 92%
“…Moreover, although very few studies regarding HL-HRQoL association were available from children and adolescents worldwide, such a positive HL-HRQoL relationship observed in our study was also in line with that reported among children and adolescents in similar studies from Virginia of USA [ 22 ], Belo Horizonte city of Brazil [ 23 ] and Chongqing city of China [ 24 ]. However, the age-groups of participants were different between our study and the three mentioned above [ 22 24 ]. Participants were students aged 11–13 years in the Virginia study [ 22 ], 15–19 years in the Belo Horizonte study [ 23 ] and 12–15 years in the Chongqing study [ 24 ], while participant’s age ranged widely from 9 to 17 years in our study.…”
Section: Disscussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Health literacy (HL) is recognized widely as a strong factor for the health outcome and HBs in adolescence [33][34][35][36][37][38]. WHO defined HL as a person's capacity to obtain and comprehend health information and services, as well as to use this information to make better health decisions [39].…”
Section: Introductionmentioning
confidence: 99%